The Center for Technology and Innovation Support of V. Ya. Shishkov Altai Regional Universal Scientific Library: outcomes and perspectives - E. К. Vekman (Библиосфера, 2019)
The article reviews the activities of the Center for Technology and Innovation Support (CTIS) set up within V. Ya. Shishkov Altay Regional Universal Scientific Library aimed at organizing and holding events that contribute to the patent-information support system formation and progress for the regional innovative development. The author emphases work features and priorities of the library-based CTIS, formulates some proposals for their further development.